2011
DOI: 10.1111/j.1748-3743.2010.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights gained through Marte Meo counselling: experiences of nurses in dementia specific care units

Abstract: This study indicates that MMC helped the nurses to gain knowledge about how to improve interactions with residents suffering from dementia. Further research is warranted into the effectiveness of MMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 15 publications
0
28
0
1
Order By: Relevance
“…Sixteen studies were quantitative, one study was qualitative, and two studies utilized mixed methods . The qualitative study used content analysis to assess perspectives after implementing a training video.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixteen studies were quantitative, one study was qualitative, and two studies utilized mixed methods . The qualitative study used content analysis to assess perspectives after implementing a training video.…”
Section: Resultsmentioning
confidence: 99%
“…Those studies indicated significant differences in attitudes prior the training program ( M = 4.21, SD = 0.29; M = 20.28, SD = 6.67) and 4 months ( M = 4, 57, SD = 0, 21, p < .001) or 6 months ( M = 28.83, SD = 5.34, F (1, 61) = 5.07, p < .05) after the intervention. Additionally, nurses felt increased satisfaction in caring for PwD because their role as nurses was informed and enriched—increasing their ability to realize the full value of patient interaction . Furthermore, after program implementation, attendees reported gains in knowledge regarding the recognition, assessment, and communication with PwD (83%, n = 540) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Marte Meo has a growing evidence base with a host of positive outcomes across various populations with regard to parenting (Osterman, Möller and Wirtberg, ; Vik and Rohde, ) and adult caregiving (Einang Alnes, Kirkevold and Skovdahl, ). The vast majority of research focuses on mothers, and very little research to date has examined the potential benefits of strengthening men's development as fathers and their ability to support the development of their children.…”
Section: Discussionmentioning
confidence: 99%